PENGARUH PROFESIONALISME TERHADAP KINERJA GURU SMP NEGERI 6 PERCUT SEI TUAN - Tarigan, Mida Aprilina (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2020)
Teacher performance is a very influential factor in the development of students' abilities. Good teacher performance will give good results to students. Professionalism is one factor that influences teacher performance. The purpose of this study was to determine and analyze the effect of professionalism on teacher performance in SMP Negeri 6 Percut Sei Tuan. This type of research is descriptive quantitative and its nature is explanatory. The population in this study was 37 respondents. In this study the entire population was sampled, amounting to 37 respondents. Data analysis technique is a simple linear regression using the SPSS program. The results of this study indicate that professionalism has a positive and significant effect on teacher performance in SMP Negeri 6 Percut Sei Tuan. The coefficient of determination (R-Square) is 0.360 or 36%. This shows that Teacher Performance (Y) can be explained by Professionalism (X) by 36% while the remaining 64% is explained by other variables not examined in this study.